The effect of S-functionalized and vacancies on V2C MXenes as anode materials for Na-ion and Li-ion batteries - Li, Ya-Meng; Guo, Yong-Liang; Jiao, Zhao-Yong (Current applied physics, 2020)
The electrochemical properties of V2C and V2CT2 (T = O, S) MXenes with and without vacancy as anode materials for Na-ion and Li-ion batteries, have been studied using first-principles calculation. The present results indicate that the adsorption strength of Li-ion and Na-ion on V2CS2 are less than that of O-functionalized, together with a lower diffusion barrier. Simultaneously, V2CS2 monolayer exhibits lower open-circuit voltage (OCV) values of 0.72 and 0.49 V for Li- and Na-ion, respectively. Interestingly, the presence of atomic vanadium vacancy on V2CS2 monolayer exerts more prominent effects on enhancing adsorption strength than that of carbon vacancy for Li-ion and Na-ion, but with an exception for the diffusion of Li-ion and Na-ion on V2CS2 monolayer. The finding suggests that the V2CS2 monolayer is expected to be a potential candidate as anode material for Li-ion and Na-ion battery due to its lower open-circuit voltages and diffusion barriers. [Display omitted] •The S-group decreased the adsorption ability of Li- and Na-ion on V2C than O-group.•The vacancy has no effects to Li- and Na-ion diffusion property on V2CS2 monolayer.•The S-group significantly reduces the high diffusion barrier of Na-ion.•The storage capacity of Li- and Na-ion reaches to 301.12 mAh/g for V2CS2 monolayer.